1999
DOI: 10.1080/07060669909501204
|View full text |Cite
|
Sign up to set email alerts
|

Viability of oospores ofPhytophthora infestansunder field conditions in northeastern North America

Abstract: Studies were conducted in potato fields on Prince Edward Island (PE) and New Brunswick (NB) to determine the overwintering viability, germination, and infectivity of oospores of Phytophthora infestans. Oospore viability was determined using plasmolysis (4 M NaCl) and tetrazolium bromide (MTT) tests. After seven months exposure to winter conditions in potato fields, the viability of oospores buried on PE and NB ranged from 2.5 to 13% and from 1 to 28%, respectively, with the plasmolysis test and from 13 to 44% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
20
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 19 publications
8
20
3
Order By: Relevance
“…After 21 days of incubation, oospores and hyphae of each cross were mechanically separated by blending the mycelia in 50 mL sterile deionized water (SDW) for 1 min. One mL 1% lysing enzyme (Sigma, L‐2665, St Louis, MO, USA) was added to 9 mL oospore suspension to eliminate mycelia and remaining sporangia (Medina & Platt, 1999). Samples were incubated at 20°C for 48 h, mixed with an equal volume of freshly prepared 0·5% KMnO 4 solution (Chang & Ko, 1991), and afterwards agitated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…After 21 days of incubation, oospores and hyphae of each cross were mechanically separated by blending the mycelia in 50 mL sterile deionized water (SDW) for 1 min. One mL 1% lysing enzyme (Sigma, L‐2665, St Louis, MO, USA) was added to 9 mL oospore suspension to eliminate mycelia and remaining sporangia (Medina & Platt, 1999). Samples were incubated at 20°C for 48 h, mixed with an equal volume of freshly prepared 0·5% KMnO 4 solution (Chang & Ko, 1991), and afterwards agitated for 15 min.…”
Section: Methodsmentioning
confidence: 99%
“…Viability was highest in the newly formed, as compared to the buried, oospores declining over time after burial. Pittis & Shattock (1994), Drenth et al (1995), Zarzycka & Sobkowiak (1997), Medina & Platt (1999) and Mayton et al (2000) also recorded adverse effects of burial period on oospore viability. In reported studies, the extent of viability varied from region to region, being 7.8% after 10-months burial in UK (Pittis & Shattock, 1994) and 5-15% after 12 months in Prince Edward Island, Canada (Medina & Platt, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…It is now well known that the two mating types when inoculated either in equal proportion or in proportions ranging up to 19:1 on host tissue produce oospores in abundance (Frinking et al, 1987;Mosa et al, 1991;Drenth et al, 1995;Cohen et al, 1997;Turkensteen et al, 2000). Recent investigations have shown that P. infestans produces oospores naturally in host tissue where the two mating types are present (Flier & Turkensteen, 1999;Medina & Platt, 1999;Gavino et al, 2000). The present paper describes (i) the role of ambient r.h. and moisture content of host tissue on oospore production, (ii) oospore survival and germination under natural conditions, and (iii) the role of oospores as primary inoculum for late blight in the temperate highlands and sub-tropical plains of India.…”
Section: Introductionmentioning
confidence: 86%
“…Occurrence of both A 1 and A 2 strains at the same location has also opened up the possibility of development of thick walled oospores which could survive extreme winter (Medina and Platt 1999 ) or summer conditions. The oospores may act as an another source of primary inoculum, in addition to the already known sources such as infected seed tubers, waste heaps and volunteer plants etc.…”
Section: The Pathogenmentioning
confidence: 98%